Women and Industrial Relations Theory : No Room in the Discourse - Forrest, Anne (Relations industrielles / Industrial Relations, 1993)
Increased international competition has produced various initiatives world-wide for new approaches to industrial relations. This author's recently completed survey ofjust under 1,000 unionized firms in Canada reveals that new initiatives and traditional industrial relations practices frequently run parallel with each other. Drawing upon the results of this survey, this paper draws out the essential elements of the changing nature of industrial relations.In particular it examines the important link between industrial relations and human resource management. The main thrust of the paper examines the ways and the extent to which pragmatic initiatives at the firm-level point towards a transformation in Canadian industrial relations.